Magical Realism for Non-Believers : A Memoir of Finding Family - Fajardo, Anika (Book collections on Project MUSE., 2019)
"Magical Realism for Non-Believers is set against the backdrops of Colombia and the United States (particularly Minneapolis) of the mid-1990s, and flashes back to the unsettled freedoms of the 1970s. It's the story of a half-Colombian, half-Minnesotan exploring her past and discovering her future, taking readers on a journey from the US to Fajardo's birthplace in Colombia and the discovery of a half-brother she never knew existed, to the creation of her own family in Minneapolis"--